Word cloud analysis for the urgency of the role of islamic schools headmaster in merdeka curriculum implementation - Mokh Fathoni; Syarifuddin (Balai Diklat Keagamaan Ambon, 2024)
The government will be hoping for Islamic schools to prepare themselves for the implementation of a Merdeka curriculum to improve the quality of education in Islamic Schools. However, until now, the implementation of the Merdeka curriculum for Islamic Schools in Ambon City has not been optimal. This research aims to describe the causes, obstacles, and solutions in the implementation of the Merdeka curriculum of the Islamic Schools in Ambon City. This study is qualitative research in the form of a review of journal articles from the Google Scholar website. The number of journal articles found was 100, then 30 with the keyword